Akuntabilitas Pengelolaan Anggaran Pendapatan dan Belanja Desa (APBDes) di Desa Tegal Mengkeb - Prasetyani Utari, Putu Ayu Mirah; Yudartha, I Putu Dharmanu; Putri Wirantari, I Dewa Ayu (CITIZEN CHARTER, 2019)
ABSTRACT Today the responsibility for accountability is not only in the central or regional governments, but also in the same authority in terms of realizing good and accountable governance. The research objective to be achieved is to discuss the Accountability of Village Income and Expenditure Management (ABPDes) in Tegal Mengkeb Village in 2018. This study uses exploratory exploration methods with techniques for changing data inzthe form of interviews, observations and evaluations. Accountability used in this study is divided into five indicators namely administrative accountability, legal accountability, political accountability, professional accountability, and moral accountability. The results of this study reveal the accountability proposed in village financial management in Tegal Mengkeb Village which in general has gone well, is still discussing some weaknesses that must be addressed immediately. It is expected that the future implementation will be more transparent and accountable in terms of the management of the Regional Budget. Keywords:Accountability, APBDes, Village Government, Village Financial Management